Tom Clancy : shadow of the dragon - Cameron, Marc (G.P. Putnam's Sons, 2020)
"When a high-level mole infiltrates American Intelligence, President Jack Ryan dispatches John Clark and the Campus team to track down a missing scientist who holds critical aerospace and naval technology"--